PELAKSANAAN KOORDINASI DALAM MENINGKATKAN KESERTAAN PRIA BER-KB DI KELURAHAN BANGKA BELITUNG DARAT KECAMATAN PONTIANAK TENGGARA - E.21111094, Erwindi (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
The problem in this study is the absence of good cooperation between extension workers family planning officer with the public, especially with men / husbands . Another problem is the lack of clear division of tasks in the implementation of family planning programs Men . The low power communication skills at field level implementers ( Extension Family Planning ) in providing information about family planning issues man . Furthermore, the lack of certainty in the form of the organization implementing the Village level Pontianak Pacific Islands Southeast District of the Army that handles planning programs , because of the lack of adequate political support . From the results of the study found that vertical coordination in the implementation of family planning male participants in the Village of the Pacific Islands to improve the planning participants Army men are still low . This is partly influenced by the decentralization policy which resulted in the BKKBN vertical coordination is not optimal because the leader comes from outside the BKKBN BKKBN . BKKBN internal conditions that still need to be addressed after the change of leadership also resulted in horizontal co-ordination with various agencies less attention . Currently coordination meeting with related elements such as scholars , public figures , and related agencies together to discuss about the operation of the family planning program had not been done . The factors that are impediments to keikutan involving the KB for men include low awareness pengetahunan and men , economic factors , the lack of support for his wife , family planning supply factors , output services ( access , quality of service , image ) , the limited choice for men kontarsepsi , belief that family planning is religiously prohibited , as well as less than optimal role of government in promoting and facilitating KB KB man man . Responding to the suggestion that there is a phenomenon which recommended , among others : 1 ) The Government in the District of East Pontianak , particularly in the Pacific Islands Village is expected to continue to increase vertical and horizontal coordination in order to increase the ranks of men planning participants . This can be done by improving employee performance BKKBN and enhance cooperation with relevant agencies , including the ranks of employees in the Village of the Pacific Islands in conducting family planning counseling men . 2 ) governments and citizens in the Village of the Pacific Islands are expected to cooperate in overcoming various obstacles in keikutan involving the family planning for men . This can be done by increasing awareness of the spread of true information about KB men that the men are interested in family planning . The government is also advised to increase access to family planning services in the Village of Bangka Belitung man that guy needs family planning acceptors in the region can be met.Â Keywords : Coordination , Participation , HusbandsÂ KB